Antimicrobial and Antioxidant Activities and Phytochemical Analysis of Rosmarinus officinalis L. Pod and Thymus vulgaris L. Leaf Ethanolic Extracts on Escherichia coli Urinary Isolates - Ahmed Alrasheed, Amel; Ahmed Alrasheid, Ayat; Mohamed Abdalla, Wafaa; Mohammed Saeed, Samar; Haidar Ahmed, Hind (International Journal of Microbiology, 2023)
The indiscriminate use of antibacterial agents has resulted in one of the largest recent global health problems, which is the emergence of bacterial resistance. This study aimed to examine the antimicrobial and antioxidant activities of ethanolic extracts of the two medicinal plants; Rosmarinus officinalis pods and Thymus vulgaris leaves on Escherichia coli urinary isolates. Both plants were extracted by absolute ethanol, and various concentrations (100, 50, 25, and 12.5 mg/ml) of the ethanolic extracts were prepared and tested against 53 urinary isolates of E. coli. An antibiotic susceptibility test was performed using chloramphenicol, gentamycin, amoxicillin, ceftriaxone, and ciprofloxacin against isolated bacteria. The antioxidant activity was measured using the DPPH method. The chemical analysis of both extracts was determined using gas chromatography-mass spectrometry (GC/MS) technique. The results showed that 88.7% of the isolated bacteria were sensitive to chloramphenicol and 87% were sensitive to gentamycin, while all isolates were resistant to amoxicillin, 13% of E. coli isolates were found to be multidrug-resistant (MDR). The inhibitory zone of R. officinalis extract against E. coli ranged between 8 and 23 mm and for T. vulgaris extract ranged between 8 and 20 mm at concentrations between 25, 50, and 100 mg/ml. The MIC of both extracts against isolates is between 12.5 and 50 mg/ml, while the MBC is between 50 and 100 mg/ml. The DPPH radical scavenging potential of T. vulgaris was 83.09%, followed by R. officinalis (81.26%). The chemical analysis by GC-MS of R. officinalis showed that the most active compounds were: eucalyptol (18.57%), bicycloheptan (10.01%), and octahydrodibenz anthracene (7.44%) and for T. vulgaris the most active compounds were: thymol (5.7%), phytol (7.92%), and hexadecanoic acid (18.51%). R. officinalis and T. vulgaris ethanolic extracts possessed antimicrobial and antioxidant activities and were found to be rich natural sources of active constituents used as traditional medicine.